Congenital Cystic Adenomatoid Malformations Type 1: Case Report - Febriani, Andi Dwi Bahagia; Shoraya, Nurul Sylvana; Alasiry, Ema (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Congenital cystic adenomatoid malformation (CCAM) is a group of multicystic and non-cystic masses due to abnormal lung development. The incidence ranges from 1: 10,000 to 1: 35,000 pregnancies. CASE REPORT: We report a case of a 3-day male baby presented with worsening respiratory distress, X-ray and chest CT were suggestive of CCAM, and sepsis. CONCLUSION: The current case adds to the collective clinical and radiological knowledge of this rare congenital lung disorder.